TEMA: Evaluación de los incrementos de peso en producción de hembras broilers con tres densidades poblacionales en condiciones de trópico ecuatoriano. - Peralta Caicedo, Stanley José (2018)
VIII. SUMMARY The present experimental work was carried out in the city of Babahoyo in the poultry production laboratories located in the Babahoyo Technical University of the Babahoyo canton at kilometer 7.5 of the Babahoyo-Montalvo road in the Province of Los Ríos, Ecuador. Whose geographical location are 01º 47 "49" south latitude and 79º 32 "west longitude, 7 meters above sea level. The humid tropical climate zone, average annual temperature of 25 ºC. Annual rainfall 74 mm, and relative humidity of 76%. The experimental work had a duration of 42 days and 300 female broiler chickens were used, 150 of the Cobb 500 line and 150 of the Ross 308 line, distributed in three densities respectively, which were (12, 13, 14 chickens per m2). ), with two presentations of food Flour and Pellets, in total there were 12 treatments respectively with 25 animals in each treatment. The purpose of this experimental work was to evaluate the productive performance of the two lines in terms of the density used and the evaluation of the weight gains of both lines under study, the results of this work were analyzed in the statistical program SPSS Statistics 23. The weight per week of each animal per treatment was also recorded, food consumption was recorded, obtaining a greater consumption of food in the Cobb 500 line. In the economic analysis, I reported that the Ross 308 line obtained a better percentage of utility which was of 25.65% Density Gains of weight Feeding